Strategic Formulation Analysis for Building Digital-based Training and Coaching Institutions in Indonesia - Wibowo, Budi; Hamdi, Edi; Indradewa, Rhian; Munandar, Agus (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research focuses on formulating strategies to support the digitalisation of MSME training and coaching institutions in Indonesia, a crucial sector that supports national economic growth. Through the use of survey methods and secondary data analysis, the research identifies key factors that influence digital adoption in these institutions and formulates effective strategies to overcome barriers. The results show that training and coaching that focus on the specific needs of MSMEs, as well as the integration of information technology, can improve the digital competence and operational effectiveness of MSMEs. A post-training coaching strategy, identified through QSPM as the more attractive option, is recommended to be implemented to optimise the growth potential of MSMEs in the digital era.